On Narco‐coyotaje: Illicit Regimes and Their Impacts on the US–Mexico Border. Issue 5 (6th October 2016) - Slack, Jeremy; Campbell, Howard
Abstract: Many have debated whether or not human smugglers, known as coyotes, are involved with drug trafficking organizations. Scholars have largely rejected so‐called "narcocoyotaje", however; we hope to problematize this narrative by adding a new theoretical layer to the discussion. Namely, we explore the ways in which different criminal activities produce hierarchies and control illicit activities within the clandestine geography of the US–Mexico border. These "illicit regimes" operate against the State, creating a hierarchy that dominates other illicit activities in order to maximize profit, avoid detection and consolidate power. While other studies have explored the relationships between the State and illicit practices this article takes the relationship between two illicit industries as its object of study. Doing so will help us move past the simply binary question about whether or not coyotes are involved with drug cartels, and allows us to understand what is being produced by this relationship, and its consequences for everyone involved.